Todorov’s Five Stages of Narrative in The Little Mermaid Folktale - wiruma Adi; Fadia Arbaatunnisa; Unpris Yastanti; Fitriyah Fitriyah (LPPM Universitas Bina Sarana Informatika, 2026)
This study analyses Hans Christian Andersen’s The Little Mermaid using Todorov’s five stages of narrative: equilibrium, disruption, recognition, repair, and new equilibrium. The research aims to explain how the narrative structure contributes to the development of themes, character growth, and moral values in the story. Data were collected from the original folktale text and analysed qualitatively through content analysis based on Todorov’s narrative framework. The analysis focused on identifying key events, character actions, and plot transitions, which were then classified according to Todorov’s five narrative stages. The findings show that the folktale follows all five stages, beginning with the mermaid’s peaceful life under the sea and continuing through conflict, sacrifice, and spiritual transformation. The study also shows that the mermaid evolves from a curious young princess into a selfless character who prioritizes compassion over personal happiness. In addition, the story reflects moral values related to sacrifice, unconditional love, and spiritual growth. Overall, this study shows that Todorov’s theory can help explain how folktales construct meaning and continue to communicate ethical and cultural values across generations.